The Effect of Celebrity Endorsements on Purchase Intention through Brand Image and Brand Awareness: Study on Scarlett Whitening Skincare consumers - Jannatul Firdaus; Sudarmiatin; Agus Hermawan (CV ODIS, 2022)
Entrepreneurs use endorsements through social media. This study aims to determine the effect of celebrity endorsement on purchase intention through brand image and brand awareness. This study was quantitative research using SPSS 25. The population in this research was potential consumers who knew about the Scarlett brand. Moreover, the sample in this research was 300 respondents. In addition, to test the instrument's feasibility, validity, and reliability tests, classical assumption tests, and hypothesis testing—the analysis technique path analysis. The results of this research show that (1) celebrity endorsement has a positive and significant direct effect on brand image and brand awareness, (2) celebrity endorsement does not have a positive and significant direct effect on purchase intention, and (3) brand image and brand awareness have a positive and significant direct effect on purchase intention, (4) celebrity endorsement has a positive and significant indirect effect on purchase intention through brand image and brand awareness. Based on the study results, similar business actors suggest that companies should be more selective in using celebrities who promote their products; besides, they should pay attention to exciting content.